Elevated expression of cholesterol transporter LRP-1 is crucially implicated in the pathobiology of glioblastoma - N. R., Shruthi; Behera, Minakshi M.; Naik, Sanoj Kumar; Das, Sunil Kumar; Gopan, Sooraj; Ghosh, Amit; Sahu, Rabi Narayan; Patra, Susama; Purkait, Suvendu (Frontiers in Neurology, 2022)
Glioblastoma (GBM) is the most common primary malignant brain tumor with a grave prognosis. The present study evaluated the expression of Cholesterol transporters [Lipoprotein Receptor-related Protein-1 (LRP-1) and ATP-binding cassette transporters-1 (ABCA-1)] in GBM and their implications in tumor-biology, clinical outcome and therapeutic potentials. The mRNA and protein expression was assessed by qRT-PCR and immunohistochemistry, respectively, in 85 GBMs. For comparison, 25 lower-grade astrocytomas (IDH-mutant, grade-2/3) [LGA] 16 cases of high-grade astrocytomas (IDH-mutant, grade-4) [HGA] were also evaluated. In-vitro analysis was performed on U87MG and LN229 glioma cell line. The expression of LRP-1 (mRNA and protein) was significantly higher in GBM than LGA, HGA and normal brain (NB) [p-values 0.007, 0.003 and <0.001 for mRNA; 0.024, <0.001 and <0.001 for immunohistochemistry). Majority of the GBMs (82.4%) showed strong immunoreactivity for LRP-1, and all tumor cases were positive while the normal brain was negative. LRP-1 immunoreactivity positively correlated with the MIB-1 labeling index (p-value-0.013). LRP-1 knockdown in-vitro was associated with decreased cell survival, proliferation, migration, invasion, and increased apoptosis, Similar effect was also demonstrated by Receptor Associated Protein (RAP), a LRP-1 inhibitory drug. The effect of RAP was almost similar to the siRNA-mediated knock-down. The ABCA-1 expression was higher in GBM than LGA and NB (p-value 0.011 and <0.001), however there was no significant association with other parameters. The expression of LRP-1 and ABCA-1 didn’t correlate with overall survival. Hence, LRP-1 is crucial for the tumor cells' survival and aggressive biological behavior. Considering its immune-positivity only in the neoplastic cell and strong positivity in GBM it may be a useful adjunct to the diagnosis. For the first time, the present study emphasized its role as a potential therapeutic target in the form of RAP which is presently being used in other neurological diseases.